Implementasi Model SAMR (Substitution, Augmentation, Modification, Redefinition) di MI Al-Ishlah Glagah Lamongan - Khoirun Niswatin; Husniyatus Salamah Zainiyati (TADRIS: Jurnal Pendidikan Islam, 2020)
Educational technology is an applied discipline that develops according to the needs and demands of society. SAMR is a Computer technology-based learning model popularized by Ruben Puentedura. The purpose of this study is to provide an alternative for educators to be able to integrate technology. This research method uses qualitative methods with data collection techniques through interviews, observation,  and online documentation. The results of this study found that the SAMR learning model is not new in the world of education in the country. SAMR has similarities with bloom's taxonomic theory, which has a stage that to like a ladder. So this discussion is exciting to be researched and implemented at elementary level students. AbstrakTeknologi pendidikan merupakan suatu disiplin ilmu terapan yang berkembang sesuai kebutuhan dan tuntutan masyarakat. SAMR  merupakan model pembelajaran berbasis teknologi komputer yang di populerkan oleh  Ruben Puentedura. Tujuan penelitian ini adalah untuk memberikan alternative kepada pendidik agar dapat mengintegrasikan tehnologi ke dalam pembelajaran. Metode penelitian ini menggunakan metode kualitatif dengan tehnik pengumpulan data melalui wawancara, observasi dan dokumentasi secara online. Hasil penelitian ini menemukan bahwa model pembelajaran SAMR ini bukanlah hal baru dalam dunia pendidikan di tanah air, SAMR memiliki kesamaan dengan teori taksonomi bloom yang memiliki tahapan yang diibaratkan seperti anak tangga. Sehingga pembahasan ini menarik untuk diteliti dan diimplementasikan pada siswa tingkat dasar.